The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1097/prs.0000000000005904
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Breast Cancer Provider Discussion Law on Breast Reconstruction Rates in New York State

Abstract: Background: New York State passed the Breast Cancer Provider Discussion Law in 2010, mandating discussion of insurance coverage for reconstruction and expedient plastic surgical referral, two significant factors found to affect reconstruction rates. This study examines the impact of this law. Methods: A retrospective cohort study of the New York State Planning and Research Cooperative System database to examine breast reconstruction rates 3 years before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Reconstruction rates increased significantly for AA women after implementation of the law, demonstrating the effectiveness of provider-driven patient education. 29 With previous studies describing differences in referral for surgery, geographical access to reconstructive surgeons also has been explored in the literature. In 2017, Bauder et al compared inpatient and ambulatory surgery data from ten states and demonstrated that higher plastic surgeon density was positively correlated with breast reconstruction rates.…”
Section: Access To Breast Reconstructionmentioning
confidence: 99%
“…Reconstruction rates increased significantly for AA women after implementation of the law, demonstrating the effectiveness of provider-driven patient education. 29 With previous studies describing differences in referral for surgery, geographical access to reconstructive surgeons also has been explored in the literature. In 2017, Bauder et al compared inpatient and ambulatory surgery data from ten states and demonstrated that higher plastic surgeon density was positively correlated with breast reconstruction rates.…”
Section: Access To Breast Reconstructionmentioning
confidence: 99%
“…In patients who elect to undergo breast reconstruction, the improvement in quality of life for many is substantial 5–7. As access to reconstructive breast care has increased in the USA, the rate of breast reconstruction following mastectomy has dramatically increased over the past 20 years 8 9. However, despite increasing overall rates of reconstruction, rates of breast reconstruction vary in different patient populations and due to different institutional structures 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that patient‐provider discussions have a significant impact on patient decisions to undergo procedures (1,2). Therefore, counseling the patient about bariatric surgery as a treatment option in outpatient settings is expected to be a crucial step in a patient’s decision to undergo the procedure (3,4), and survey studies have found that patients are more likely to undergo bariatric surgery when it is recommended by their health care provider (5).…”
Section: Introductionmentioning
confidence: 99%